Digitalization of the economy as a dominant factor in the transformation of management systems of construction enterprises - Fedorchenko, M.; Katin, O. (Ways to Improve Construction Efficiency, 2025)
The digitalization of the economy has become a decisive factor in modern transformations across all sectors of economic activity, particularly in construction, where management processes require new approaches to ensure the sustainability and competitiveness of enterprises. The transition to digital models of functioning is not limited to automation of operations or the implementation of information technologies; it implies a profound change in the management paradigm that encompasses organizational structures, business processes, communication models, and methods of value creation. In the construction business, digitalization acts as a catalyst for change, as the industry is characterized by high capital intensity, long project implementation timelines, and the need for coordination among numerous stakeholders. The digital economy enables the formation of new management models based on the use of cloud technologies, big data, artificial intelligence, blockchain platforms, and visual modeling systems (including BIM). Combined with integrated ERP solutions and business analytics systems, these tools create conditions for greater transparency, predictability, and efficiency in managing construction projects. They allow real-time monitoring, resource optimization, and the development of adaptive scenarios that account for risks. The significance of digitalization also lies in transforming management logic. Whereas the traditional model relied on post-factum analysis of results, modern digital approaches emphasize preventive management and the use of predictive analytics. This reduces the likelihood of deviations from plans and enables timely responses to external challenges. In construction, this translates into more accurate cost and schedule forecasts, fewer errors during project implementation, and enhanced safety. Moreover, digitalization reshapes stakeholder interaction by creating unified communication environments that allow clients, designers, contractors, and investors to collaborate based on shared data and digital models. This increases trust among participants, reduces transaction costs, and ensures greater consistency in decision-making.